Ensinando mulheres a fortalecer a musculatura perineal: estudo da efetividade do uso de automonitoramento na prática de exercícios - Negri, Aline Fernanda (2014)
Urinary incontinence is a condition of loss of bladder control that causes several changes in the social life of women. The treatments offered to these women include medical, surgical and behavioral treatment. This study followed four women with stress urinary incontinence, instituting behavioral therapy as treatment and using behavioral analysis as a method. Aiming to check the change in muscle strength with the guidance of a program to strengthen the muscles of the perineum, alternating the use of self-monitoring. Conducting weekly individual consultations at different times for each participant, 6-14 weeks of follow-up period. The data were analyzed and compared individually for each participant. At the end of the follow three participants obtained higher values in the objective assessment of muscle strength compared with the original, the four women had higher values in the subjective assessment of muscle strength of the muscles of the perineum and all reported improvement of symptoms. Self-monitoring was considered an important tool to monitor these women